Quantifying topographical changes in muscle activation: A statistical parametric mapping approach - Pincheira, P. A.; Martinez-Valdes, E.; De la Fuente, C.; Palma, F.; Valencia, O.; Redenz, G.; Guzman-Venegas, R. (Proceedings, 2020)
Regional changes in muscle activation occur at different contraction intensities. These changes can be observed with activity maps created with high-density electromyography (HDEMG). When quantifying these changes, statistical parametric mapping (SPM) is a neuroimaging technique that may be used to perform statistical analyses with high sensitivity and spatial resolution. The aim of this study was to identify regional changes in muscle activation at different contraction intensities, comparing SPM and the HDEMG barycenter (centroid). Twelve participants performed plantar flexion isometric contractions at 20%, 40%, and 60% of the maximal voluntary contraction (MVC), while HDEMG was recorded from the medial gastrocnemius. An SPM repeated measures ANOVA design revealed specific mediolateral and cephalocaudal changes in muscle activation with increasing contraction intensities, which were not clearly detected by the variation in the barycenter coordinates. Only SPM revealed statistically significant nonuniform changes in EMG amplitude between all increasing levels of muscle activation.